Sagot :
Answer:
1. (8a² + 2b + 12) +(4a² - 5b + 9)
=8a+2b+12+4a²-5b+9
=8a-3b+12+4a²+9
=8a-3b+21+4a²
2. (-3c³ + 9c - 5) + (11c³ - 15)
=-3c³+9c-5+11c³-15
=8c³+9c-5-15
=8c³+9c-20
3. (3d² + 4e - 1) - (-6d² + 8e - 7)
=3d²+4e-1+6d²-8e+7
=9d²+4e-1-8e+7
=9d²-4e-1+7
=9d²-4e+6
4. (4f³ + 5f² - 20f) - (10f² + 19f - 70)
=4f³+5f²-20f-10f²-19f+70
=4f³-5f²-20f-19f+70
=4f³-5f²-39f+70
5. (4g² + 5g + 10) + (4g + 60)
=4g²+5g+10+4g+60
=4g²+9g+10+60
=4g²+9g+70
6. (-9h² + 2h - 25) + (8h - 18)
=-9h²+2h-25+8h-18
=-9h²+10h-25-18
=-9h²+10h-43
7. (15j³ - 4j + 13) + (j³ + 16j - 19)
=15j³-4j+13+j³+16j-19
=16j³-4j+13+16j-19
=16j³+12j+13-19
=16j³+12j-6
8. (13k² + 5k -21) + (5k² + 17k³ - 24)
=13k²+5k-21+5k²+17k³-24
=18k²+5k-45+17k³
=17k³+18k²+5k-45
9. (7l² - 14l + 10) + (15l² + 14l - 16)
=7l²-14l+10+15l²+14l-16
=7l²+10+15l²-16
=22l²+10-16
=22l²-6
10. (15m²n + 8mn - 3n) - (15m²n - 34mn + 5n)
=15m²n+8mn-3n-15m²n+34mn-5n
=8mn-3n+34mn-5n
=42mn-3n-5n
=42mn-8n
Step-by-step explanation: